MIGRASI DAN XENOFOBIA: ANALISIS KEBIJAKAN MIGRASI TERTUTUP HONGARIA ERA PERDANA MENTERI VIKTOR ORBÁN - Firsty Chintya Laksmi Perbawani (Halu Oleo University, 2022)
Hungary is a European Union (EU) member state that has received international attention for its migration policy. While other EU member states assisted each other in accepting the refugee relocation program in response to Europe's immigration crisis, Hungary refused it. This cannot be separated from Prime Minister Viktor Orbán's leadership figure. As a result, the purpose of this article is to analyze why Hungary's migration policy is so stringent and restrictive. Using framing theory and qualitative analytical methodologies, this article proves that the Hungarian government purposefully constructed a xenophobic narrative platform. Furthermore, the renewal of migration strategies has always been restricted, as evidenced by the existence of: amendments to the Government Decree and the Asylum Act; rejection of the EU's mandatory quota system; and the existence of a selective-racism and deeply-rooted racism within the Hungarian state.